Peran Digital Marketing dalam Pembentukan Jaringan Bisnis UMKM Lampu Hias Bandung di TikTok - Mia Sri Rezeki; Rismawati Putri; Andini Sabilah; Sandi .; Candra Maulana (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid development of digital technology has significantly transformed how micro, small, and medium enterprises (MSMEs) conduct marketing activities, particularly through social media platforms. This study aims to analyze the role of digital marketing via TikTok in forming and expanding the business network of Klasik Lampu Hias MSMEs in Bandung. The research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation of digital marketing activities implemented by the enterprise. The findings reveal that the use of TikTok—through visual content, storytelling of the production process, audience interaction, and live streaming features—has successfully increased sales, expanded market reach, and facilitated the development of business relationships with various stakeholders, including customers from different regions, decoration stores, and event organizers. Digital marketing functions not only as a promotional tool but also as a strategic approach to building broader and more sustainable business networks for MSMEs.